A technology outreach campaign targeting small-scale maize producers in eastern DR Congo - Woomer, P.; Luc, B.; Bisomerine, C. (2024)
The African Agricultural Leadership Institute launched an outreach campaign to benefit smallholder maize farmers in the Ruzizi Plain and DR Congo. Packages of production inputs for 0.25 ha of maize were distributed to 2185 registered farmers. The campaign resulted in average yields of 2736 kg per ha, with a net yield of $900 per hectare and a benefit-cost ratio of $3.72 per dollar invested. The campaign covered 546 ha at a cost of $181,030, or $83 per household.